Destination image of Chitwan National Park, Nepal: Insights from a content analysis of online photographs. (March 2022) - Bhatt, Pragya; Pickering, Catherine Marina
Abstract: There are millions of publicly available photographs posted by people visiting protected areas on social media, but can they enhance our understanding of the preferences of nature-based tourists, and if so, how are such areas marketed? To explore the uses of this still novel source of data, we compared the content of photographs posted by tourists (perceived image(s)) with those posted by tourism organizations online (projected destination image(s)) using Chitwan National Park in Nepal as a case study. This involved comparing the content of 645 photographs posted online by government and tourism companies with 1214 photographs taken by tourists in the Park and posted to the social media platform Flickr. The findings highlighted similarities including the popularity of wildlife and landscapes in photographs, but also discordances in how cultural attributes were more popular in photographs posted by tourists than those promoting tourism. When the geolocations of Flickr photographs were mapped across the Park, spatial and temporal hotspots were identified relating to specific content, while the popularity of photographs with others on Flickr indicated that potential future tourists may also value wildlife and culture in the Park. The findings highlight how destination marketing online could better match what tourists shared about the Park and identify what they valued where and when in the Park. It also illustrates how other parks where nature-based tourism is economically, socially, and ecologically valuable, but resources limited, could harness free and readily available social media content to improve destination marketing and management, despite some recognized limitations with social media data. Management implications: The content of social media photographs and metadata about when and where images were taken can provide useful insights into tourist preferences. For Chitwan National Park, Nepal there were congruence in some aspects of projected (online images provided by tourism organisations) and perceived destination images from social media. This case study highlights how nature-based tourism destinations in developing countries could harness social media as a useful, low cost and time-effective way to obtain additional information about tourists. For Chitwan the results indicate how park authorities should continue to focus on wildlife and landscapes in marketing but also emphasize cultural attributes.